HUBUNGAN FAKTOR INDIVIDU DAN FAKTOR RELASI TERHADAP TINDAKAN KEKERASAN DALAM PACARAN (KDP) PADA SISWA SMA DI DKI JAKARTA TAHUN 2023 - Dhanifa Aldeana Maheswari, (2024)
Dating violence (DV) in Indonesia has been increase three times higher from 2021 to 2022. This study aimed at seeking the relation between individual factors and relation factors to DV. This is a quantitative study with a cross-sectional design conducted among six high school in DKI Jakarta. The population in this study were high school students in DKI Jakarta. The sample in this study were 550 respondents with 275 girls and 275 boys, using proportional stratified random sampling. The proportion of DV among high school students is 46,7%. There was an association between individual factor, namely experience in violence and relation factors, namely conflict resolution and infidelity to DV. This study concludes that students who had experiences of violence in childhood, a lack of conflict resolution, and infidelity were increase the risk of DV. It is highly recommended for high school students to participate in education about preventing DV, improving life skills, and get professional health to heal the past violent trauma.